Hybrid biodegradable hydrogels obtained from nanoclay and carboxymethylcellulose polysaccharide: Hydrophilic, kinetic, spectroscopic and morphological properties - Nascimento, Denis W. S. [UNESP]; De Moura, Márcia R. [UNESP]; Mattoso, Luiz H. C.; Aouada, Fauze A. [UNESP] (American Scientific Publishers, 2017)
In this paper, series of novel nanocomposite hydrogels based on polyacrylamide (PAAm), carboxymethylcellulose (CMC) and nanoclay were synthesized. Hydrophilic, kinetic, spectroscopic and morphological properties were investigated as function of their constituents. Spectroscopic properties confirmed the obtaining of the nanocomposites. It was also observed that the nanocomposites have walls of pores with a more rugged morphology compared with the morphology of the hydrogel without clay, contributing to repel the water molecules. Besides, the results showed that the velocity and quantity of water uptake may be controlled by adjusting of matrix rigidity, i.e., nanoclay content into polymeric matrix. This behavior is required to future application in agriculture fields, specifically as carrier vehicle in controlled release of agrochemicals. Thus, these nanocomposites have technological application.
Keywords: Hydrogel; Morphological properties; Nanoclay; Nanocomposite; Swelling degree